Analisa Perbandingan BBM (Bahan Bakar Minyak) Dari Limbah Plastik Menggunakan Alat Pirolisis Pemanas LPG (Liquified Petroleum Gas) dan Listrik - Rozikin, Miftachur; Balaka, Ridway; Hasbi, Muhammad (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2020)
The  purpose  of  this  research  is  to  know  the  comparison  of  fuel  (oil  fuel) pyrolysis results using LPG heaters (Liquid Petroleum Gas) and electricity. In this study using two pyrolysis tools, namely pyrolysis tools using gas and electrical heaters.  Materials used are plastic garbage types of HDPE, LDPE and PP as much as 500 grams. The results of this study showed the value of the  density  of  pyrolysis  tools  using  gas  heaters  of  790.6  Kg/m³  for  HDPE plastic, 722.0 Kg/m³ for LDPE Plastics and 738.7 Kg/m³ for PP Plastics. As for the viscosity value of 0.7853 m²/s for HDPE plastic, 0.6771 m²/s for LDPE Plastics and 0.6159 m²/s for PP Plastics. For the value of density by using the electrical pyrolysis tools are 771.4 Kg/m³ for HDPE plastic, 743.1 Kg/m³ for LDPE Plastics and 768.3 Kg/m³ for PP Plastics. While the viscosity value is  obtained  at  0.7198  m²/s  for  HDPE  plastic,  0.7613  m²/s  for  LDPE  and 0.7054 m²/s for PP plastic. Keywords: Pyrolysis, comparison of pyrolysis tools, plastics